Sistem Informasi Point Of Sales (POS) Berbasis Web Pada Rumah Makan Sambel Dadakan Gor Pakansari Menggunakan Metode Waterfall - Sheren Clever Cantika (2023)
The era of globalization, which is marked by the rapid development of information and communication technology, has had an impact on almost all human activities, such as politics, economics, social, culture, education and the business world. Likewise with the "Sambel Dadakan GOR Pakansari" restaurant, if you want to further increase your business competitiveness, the use of information and communication technology is a must. The "Sambel Dadakan GOR Pakansari" restaurant is a business that includes micro, small and medium enterprises whose business management has not yet optimized information and communication technology, so that problems arise related to transaction processes, preparation of reports, and inventory management or stock of goods. Therefore, researchers are interested in conducting research at the "Sambel Dadakan GOR Pakansari" restaurant with the title designing a web-based Point Of Sales (POS) Information System using the waterfall method. The result of this system is that the (POS) system can be used at the Sambel Dadakan Gor Pakansari Restaurant in real time so that it can contribute to increasing business competitiveness, especially sales levels.